FENOMENA ANDROGINI DI KOTA PEKANBARU - Mega Silvia; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The phenomenon of androgyny already highly developed today in the city of Pekanbaru. This phenomenon is seen with start many encountered in public places feminine men and masculine women. This study aims to determine the motives, meaning and practice of communication androgyny in Pekanbaru.This study uses qualitative research with phenomenological approach. Subjects consisted of three actors androgyny in Pekanbaru are selected using snowball technique. The study used data collection techniques of observation, interviews, and documentation of research. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The results showed that the motif of androgyny in Pekanbaru City consists of a motive because (Because motive) the environment, a sense of comfort and want to look different. While the motive (in order to motive) that wants to be accepted by society and would like to remain seen as normal. Meanings given by androgynous fashion that is as applicable to all types, balanced androgynous fashion. The communication experience categorized into two pleasant communication experience and experience unpleasant communication.Keywords: phenomenon, androgynous, motive, meaning, experience communication